Reduced renewal of conditioned suppression following lesions of the dorsal hippocampus in male rats - Tavakkoli, Armin (Behav Neurosci, 2020)
Extinguished responding will renew when the conditioned stimulus occurs outside the extinction context. Although studies of conditioned freezing have consistently demonstrated a role for the hippocampus in renewal, several studies have demonstrated intact renewal of conditioned suppression despite damage to the hippocampus (Frohardt et al., 2002; Todd et al., 2017; Wilson et al., 1995). Because these prior studies have examined renewal when testing occurred in the original conditioning context (“Context A”), the present conditioned suppression experiments examined the role of the hippocampus when testing occurred in a context not associated with prior conditioning (“Context C”). In Experiments 1 and 2, conditioning occurred in Context A, and extinction in Context B. Renewal of conditioned suppression was observed when the extinguished CS was tested in Context C. However, renewal was attenuated in rats with lesions of the dorsal hippocampus (DH). Summation testing failed to detect conditioned inhibition in the extinction context, suggesting instead that the context acquired negative occasion-setting properties. Attenuated renewal was not due to an inability of DH lesioned rats to discriminate contexts (Experiment 3). These experiments thus demonstrate a role for the DH in renewal of conditioned suppression when testing occurs in a neutral context.